ANALISIS DESKRIPTIF MOTIVASI DAN PENGALAMAN SOLO WOMEN TRAVELLER - Izmi Munauwarah; A.H Galih Kusumah; Ayulia Nirwani (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
The growing phenomenon of Solo Women Traveling in recent years reflects a shift in tourism dynamics. This study employs a literature review method, collecting data from various journals, articles, and other relevant sources to explore the motivations and experiences of solo women travelers in making the decision to travel alone. The primary motivations identified include the pursuit of freedom, independence, self-development, escape from routine, and the achievement of new life perspectives. Solo travel experiences for women often provide opportunities for introspection, enhanced self-confidence, and empowerment through cultural interactions and the management of unique challenges. However, such journeys also present various risks, including safety concerns and gender-based stereotypes. This study highlights the importance of more inclusive support systems and gender-sensitive safety measures in tourism to enhance the comfort and satisfaction of female travelers. The findings offer valuable insights for the development of more inclusive and women-friendly tourism strategies.